Polarographic Electroreduction of Uranly Ion in Glycine, DL-Asprtic Acid and Phenylalanine-Aqueous Solutions - Gomaa, E.A.; El-Askalany, A.H.; Moussa, M.N.H. (Asian Journal of Chemistry, 2010)
The electroreduction of uranyl perchlorate in presence of glycine, DL-aspartic acid and phenylalanine were studied by using DC polarography. Glycine and phenylalanine decrease slightly the limiting currents of the two reduction waves with also very small shift in their half wave potentials towards more negative values. DL-aspartic acid shift the half wave potential of the first one electron wave to more complexing direction and changes the second wave from two electron mechanism to one electron processes due to the increase of the pentavalent uranyl ion disproportionation in the presence of the last medium.